(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Miconazole nitrate is a broad-spectrum antifungal agent, poorly water-soluble drug and it is used for treatment of superficial fungal infections. Microemulgel could increase drug deposition over to the skin. Therefore, the aim of this study was to prepare 2% miconazole nitrate transparent microemulgel that contains 99% w/w liquid. Preliminary screening of oils and polymers were carried out. Oil phase of the microemulgel selected based on maximum solubility of miconazole nitrateinoil. A 23 full factorial design was used to check the effect of cinnamon oil (X1), HPMC K4M (X2) and tween 20 (X3) on viscosity (Y1) and % of cumulative drug release at 6 h (Y2). Multiple linear regression analysis, ANOVA and graphical representation of the influence factor by 3D response surface plots were performed using Design Expert 7.1.5. Checkpoint batch was prepared to validate the evolved model. Optimized batch F5 was found to be stable and it showed globule size 26±3 µm. In Ex-vivo drug permeation study batch F5 was shown 87.05±2.42% drug released after 6 h and drug deposition on the upper layer of skin was found 52.5%. Accelerated stability study showed that there was no significant change in the microemulgel parameters within three month and similarity factor f2 was found to be 91.05±1.67 %. Therefore, 2% miconazole nitrate microemulgel was providing an effective treatment against topical infections